In depth LC-ESIMSn-guided phytochemical analysis of Ziziphus jujuba Mill. leaves. (March 2019) - Masullo, Milena; Cerulli, Antonietta; Montoro, Paola; Pizza, Cosimo; Piacente, Sonia
Abstract: Ziziphus jujuba Mill. leaves are receiving a great attention for their ability to improve sleep, exerting beneficial effects for both the heart and the central nervous system. With the aim to obtain a comprehensive analysis of the specialised metabolites occurring in the leaves of Z. jujuba, a LC-ESI/(HR)Orbitrap/MS profile in negative ion mode of the methanol extract was carried out. The LC-MS profile guided the isolation of 42 compounds, of which the structures were elucidated by 1D and 2D-NMR experiments. Based on this approach, 2 previously unreported dammarane-type saponins have been characterized along with flavonoid derivatives, dammarane-type saponins and triterpenic acids. Dammarane-type saponins were tested for their cytotoxic activity against A549 and HeLa cancer cell lines. None of the tested compounds, in a range of concentrations between 12.5 and 100 μM, caused a significant reduction of the cell number. This work provides a deep insight on the chemistry of the leaves of Z. jujuba and could be useful for further biological studies aimed at identifying phytochemicals contributing to the health benefits attributed to this herbal drug. Graphical abstract: A LC-ESI/LTQOrbitrap/MS profile in negative ion mode of the methanol extract of Ziziphus jujuba Mill. leaves was performed. 42 compounds belonging to the classes of dammarane saponins, triterpenes and flavonoids were elucidated by 1D and 2D-NMR experiments. Based on this approach, two new dammarane-type saponins have been isolated. Highlights: An in-depth phytochemical analysis of Ziziphus jujuba leaves was carried out. The LC-ESI/LTQOrbitrap/MS profile of the methanol extract was acquired. The LC-MS profile showed the occurrence of 42 compounds. Dammarane saponins, triterpenes and flavonoids were elucidated by 1D and 2D-NMR. Two dammarane saponins never reported before have been isolated.